2019
DOI: 10.18203/2319-2003.ijbcp20190566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the knowledge level and usage attitudes of the medical students on the medicinal herbs and herbal products: a project of special study module in the first three years of the school of medicine

Abstract: Background: In this survey, it was aimed to determine the types of medicinal herbs and herbal products, reasons of use and consciousness levels among the medical students in the first three years of the School of Medicine.Methods: A cross-sectional descriptive questionnaire consisting of 50 questions was applied to all the students in the first three years of Dokuz Eylül University School of Medicine between September 1, 2016 and June 1, 2017.Results: The results of 571 participating students were evaluated. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…This might be due to the fact that avaiallitbiy of conventional medicine is comparatively low in Arfican countries like Ghana compared to Saudi Arabia which resulted in more consucmpiton of alternative medicine. Interestingly, another study conducted in Turkey among medical students revealed high consumption of herbal medicines (73.4 %) without having sufficient knowledge about medicinal herbs and hence the researchers recommended to increase the level of awareness among medical students [35]. Drug-herb interaction has gained enormous attention in the past few decades and it may result in harmful events in some cases [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that avaiallitbiy of conventional medicine is comparatively low in Arfican countries like Ghana compared to Saudi Arabia which resulted in more consucmpiton of alternative medicine. Interestingly, another study conducted in Turkey among medical students revealed high consumption of herbal medicines (73.4 %) without having sufficient knowledge about medicinal herbs and hence the researchers recommended to increase the level of awareness among medical students [35]. Drug-herb interaction has gained enormous attention in the past few decades and it may result in harmful events in some cases [36,37].…”
Section: Discussionmentioning
confidence: 99%